Global corporate governance - Chew, Donald H.; Gillan, Stuart L. (Columbia Business School publishing., 2009)
Effective corporate governance, or the set of controls and incentives that drive top management, originates both outside and inside the firm and assures investors who hope to commit their capital. Essential when buying stocks in one's own country, effective corporate governance is even more important abroad, where information can be less reliable and investor influence (or protection) more limited. In this collection of articles from the Journal of Applied Corporate Finance, more than thirty leading scholars and practitioners discuss the possibilities and limitations of g.